Putting Childhood in Its Place: Rethinking popular discourses on the conceptualisation of child trafficking in Ghana - Koomson, Bernard; Abdulai, Dawuda (Anti-Trafficking Review, 2021)
Popular discourses on child trafficking are generally characterised by unverifiable statistics, melodramatic representations, and emotional reactions. More so, notions of poverty, exploitation, and the protection of children from harm have driven educational and sensitisation campaigns that seek to address trafficking in children. The ensuing status quo blurs diverse cultural conceptions of childhood and its moral representations of acceptable and unacceptable labour. Drawing on qualitative data from a Ghanaian fishing community, this paper reviews the impoverished and hazardous representation of children’s transportation to other fishing communities for work. It contends that the prevailing conceptualisation of child trafficking fails to account for the socio-cultural underpinnings of children’s movement to other fishing communities for work. Consequently, this paper argues that it is important to situate popular discourses of child trafficking within fishing community’s conceptualisation of childhood in order to provide a comprehensive understanding of the phenomenon within those communities.